On the Region of Feasibility of Interference Alignment in Underwater Sensor Networks - P. Pandey; D Pompili (Proc. of IEEE Underwater Communications: Channel Modelling&Validation (UComms), 2012)
To enable underwater applications such as coastal and tactical surveillance, undersea explorations, and pic- ture/video acquisition, there is a need to achieve high data- rate underwater acoustic communications, which translates into attaining high acoustic channel spectral efficiencies. Interference Alignment (IA) technique, which has recently been proposed for radio-frequency MIMO terrestrial communication systems, aims at improving the spectral efficiency by enabling nodes to transmit data simultaneously at a rate equal to half of the interference-free channel capacity. While promising, there are challenges to be solved for the use of IA underwater, i.e., imperfect acoustic channel knowledge, high computational complexity, and high communication delay. In this paper, a feasibility study on the practical employment of IA underwater is presented, and a novel distributed computing framework for sharing processing resources in the network so to parallelize an iterative IA algorithm is proposed.